Surface protection of mild steel in acidic chloride solution by 5-Nitro-8-Hydroxy Quinoline - R. Ganapathi Sundaram; M. Sundaravadivelu (Egyptian Journal of Petroleum)
The effect of commercially available quinoline nucleus based pharmaceutically active compound 5-Nitro-8-Hydroxy Quinoline (NHQ) against the corrosion of mild steel (MS) in 1 M acidic chloride (HCl) solution was investigated by chemical (weight loss – WL) and electrochemical (Tafel polarization, Linear polarization and Electrochemical impedance spectroscopy) techniques. From all the four methods, it is inferred that the percentage of inhibition efficiency increases with increasing the inhibitor concentration from 50 to 300 ppm. The adsorption behavior of inhibitor obeyed through Langmuir isotherm model. Thermodynamic parameters were also calculated and predict that the process of inhibition is a spontaneous reaction. EIS technique exhibits one capacitive loop indicating that, the corrosion reaction is controlled by charge transfer process. Tafel polarization studies revealed that the investigated inhibitor is mixed type and the mode of adsorption is physical in nature. The surface morphologies were examined by FT-IR, SEM and EDX techniques. Theoretical quantum chemical calculations were performed to confirm the ability of NHQ to adsorb onto mild steel surface. Keywords: Acidic chloride solution, MS, NHQ, WL, SEM, FT-IR